2001
DOI: 10.1099/00221287-147-6-1671
|View full text |Cite
|
Sign up to set email alerts
|

Commensal Escherichia coli isolates are phylogenetically distributed among geographically distinct human populations

Abstract: An intraspecies phylogenetic grouping of 168 human commensal Escherichia coli strains isolated from the stools of three geographically distinct human populations (France, Croatia, Mali) was generated by triplex PCR. The distributions of seven known extraintestinal virulence determinants (ibeA, pap, sfa/foc, afa, hly, cnf1, aer) were also determined by PCR. The data from the three populations were compiled, which showed that strains from phylogenetic groups A (40 %) and B1 (34 %) were the most common, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
226
9
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(264 citation statements)
references
References 30 publications
24
226
9
4
Order By: Relevance
“…Phylogenetic grouping placed the majority of isolates into phylogenetic group A (55 %), with a significant number of isolates in group B2 (21 %). While this frequency of strains of phylogenetic group A is characteristic for faecal E. coli from a middle-European population, the frequency of phylogenetic group B2 strains is higher than in the middle-European population (Duriez et al, 2001). Earlier studies showed that commensal and virulent strains are gathered in group B2 and that potentially virulent strains of group B2 had gathered several virulence factors (Duriez et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic grouping placed the majority of isolates into phylogenetic group A (55 %), with a significant number of isolates in group B2 (21 %). While this frequency of strains of phylogenetic group A is characteristic for faecal E. coli from a middle-European population, the frequency of phylogenetic group B2 strains is higher than in the middle-European population (Duriez et al, 2001). Earlier studies showed that commensal and virulent strains are gathered in group B2 and that potentially virulent strains of group B2 had gathered several virulence factors (Duriez et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…TOB1 belongs to the phylogenetic group B2, which harbours pathogenic as well as non-pathogenic strains (Duriez et al, 2001). However, PCR tests showed that TOB1 did not harbour common virulence factors, did not express haemolytic activity and was a prototroph (Table 2, data not shown).…”
Section: Construction Of Mutants With Distinct Expression Of Extracelmentioning
confidence: 99%
“…Over the last decade, a number of authors have sought to establish the prevalence of E. coli with ExPEC potential colonising the gut by performing microbiological screening studies on the stool of healthy individuals that delineate resident E. coli strains based on their phylogroup (58)(59)(60)(61)(62)(63). Results of these studies have demonstrated that 11-48% of healthy individuals are colonised with E. coli belonging to phylogroup B2, which is traditionally associated with virulence and ExPEC infections.…”
Section: Expec As An Intestinal Colonistmentioning
confidence: 99%
“…The virulent extraintestinal E. coli strains belong mainly to group B2 and, to a lesser extent, to group D, whereas most commensal strains belong to group A [10]. Numerically, group A is the dominant group among normal fecal E. coli but relative percent distribution of these groups differs from one country to another [11,12]. In comparison with ExPEC, the human commensal fecal strains had fewer virulence factors [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Numerically, group A is the dominant group among normal fecal E. coli but relative percent distribution of these groups differs from one country to another [11,12]. In comparison with ExPEC, the human commensal fecal strains had fewer virulence factors [11,13]. Such VFs induce disease through their ability to help the organisms to avoid or subvert host defenses, colonize key anatomical sites, perturb host physiology, invade host tissues, and/or incite a noxious host inflammatory response [9,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%